Acknowledgment of Adat Law-Based Tenure in the Courtroom: Study of Decisions on Criminal Acts of Land Clearing by Burning, Logging Trees Without Permits, and Collecting Plantation Products Without Permits - Almonika Cindy Fatika Sari (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2022)
Abstract: The recognition of the existence of adat communities and their rights can not only be found in the constitution but also various regional laws and regulations. However, this recognition is counterproductive because it further distances adat communities from their rights, especially tenure rights based on adat law. The diverse and minimal understanding of adat law by executives and law enforcement officials compound this condition. Sometimes, adat communities must face the law because they are suspected of committing criminal acts violating it. Therefore, this research aimed to examine the recognition of adat communities’ tenure rights in the courtroom. This research is normative legal research using a case approach—four court decisions as the primary data. The results of this study indicated that in deciding cases, there are times when judges recognize how adat communities control and utilize natural resources according to their adat law. However, there are times when judges override the narrative of adat law that adat communities claim. This research also showed that adat law narratives can play a role in freeing adat communities from punishment. Keywords: Adat law, adat communities, criminal crime, tenure rights